1994
DOI: 10.1038/eye.1994.61
|View full text |Cite
|
Sign up to set email alerts
|

The role of natural killer cells in the development of herpes simplex virus type 1 induced stromal keratitis in mice

Abstract: Natural killer (NK) cells and acquired cell-mediated immunity effector cells (delayed type hypersensitivity (DTH) and cytotoxic T lymphocytes (CTL)) have been reported to play a vital role in the defence of the host against tumour and viral infections in locations other than the eye. A vigorous cellular inflammatory response to viral infections of the cornea, however, with the attendant damage to the corneal clarity, has obvious evolutionary disadvantages, and a substantial body of evidence indicates that in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Consequently, inflammatory-inducing events within the cornea resulting in structural modifications or corneal opacification can have devastating consequences to the quality of the visual axis. Relative to HSV-1, neutrophils (Thomas et al, 1997), macrophages (Bauer et al, 2001), Langerhans cells (Hendricks et al, 1992a), natural killer cells (Tamesis et al, 1994), and CD4 1 T lymphocytes (Gangappa et al, 1998) seemingly promote the development of herpetic stromal keratitis, which may be related to the production of IL-2 or IFN-g secreted by these cells (Hendricks et al, 1992b;Tang et al, 1997). In the present study, determining the efficacious or detrimental effects of another cytokine generated during the immune response to ocular HSV-1, IL-12, was undertaken using GFAP-IL12 transgenic mice.…”
Section: Discussionmentioning
confidence: 96%
“…Consequently, inflammatory-inducing events within the cornea resulting in structural modifications or corneal opacification can have devastating consequences to the quality of the visual axis. Relative to HSV-1, neutrophils (Thomas et al, 1997), macrophages (Bauer et al, 2001), Langerhans cells (Hendricks et al, 1992a), natural killer cells (Tamesis et al, 1994), and CD4 1 T lymphocytes (Gangappa et al, 1998) seemingly promote the development of herpetic stromal keratitis, which may be related to the production of IL-2 or IFN-g secreted by these cells (Hendricks et al, 1992b;Tang et al, 1997). In the present study, determining the efficacious or detrimental effects of another cytokine generated during the immune response to ocular HSV-1, IL-12, was undertaken using GFAP-IL12 transgenic mice.…”
Section: Discussionmentioning
confidence: 96%
“…NK cells are thought to contribute to stromal keratitis [28], control HSV-1 infection [29,30], and respond to a CXCL10 chemical gradient through the receptor CXCR3 [31]. However, similar numbers of NK cells were found residing in the cornea comparing HSV-1-infected WT (225 ± 70 cells/cornea pair), CXCL9−/− (260 ± 90 cells/cornea pair), and CXCL10−/− (190 ± 90/ cornea pair) mice.…”
Section: Cd4 + T Cell Infiltration Into the Cornea Is Reduced In Cxclmentioning
confidence: 99%
“…21 On the other hand, in C.AL-20 mice that are highly susceptible to HSV, NK-cell depletion significantly decreases the incidence and severity of HSK. 22 These observations have suggested that the roles of NK cells in HSK could produce completely different results depending on the circumstances.…”
Section: Natural Killer Cellsmentioning
confidence: 97%